Pengolahan Sinyal Fleks Sensor pada Sarung Tangan Pintar Penerjemah Bahasa Isyarat - Anton Yudhana (Annual Research Seminar (ARS), 2016)
The person with hearing impaired has difficulty speaking. It can be caused by less talk functioning of tools, such as the oral cavity, tongue, palate and ribbons sound. Besides it, or not less functioning of the organ of hearing, delayed language development, system malfunction in neuroscience and structure muscles. Also, it can be caused of the inability hearts motion control also can be lead to limitations hearts speak. This paper present signal processing of output flex sensor that attached on special glove. The glove was called smart glove based on it function to translate of sign language to sound produced by speaker. The used of accelerometer and flex sensor is to read the code of gestures to be very effective, because according to its function for reading the flexibilities of the fingers and hand gestures.